INTERNAL SUBBASINS OF THE SANGZOR RIVER BASIN: A CASE STUDY OF THE KOKJAR BASIN - Dursinovich, Qosimov Nurmukhamed (ANTIS PUBLISHER, 2025)
Objective: This study investigates the hierarchical division of the Sangzor River Basin, with a specific focus on the Kokjar Basin as one of its major internal sub-basins. It aims to describe the basin’s geographical extent, boundaries, surface morphology, soils, climate, and land-cover characteristics in relation to its natural potential for recreation and tourism development. Method: The research employed cartographic and Geographic Information System (GIS) methods to delineate basin boundaries and analyze geomorphological, hydrological, and climatic parameters. Results: The findings reveal that the Kokjar Basin, oriented north–south toward the Chumqor Mountain watershed, benefits from moist air inflow from the west, resulting in higher precipitation and increased surface runoff. Its fertile brown soils support extensive agricultural and horticultural activities, while forest and water resources promote eco-tourism opportunities. Novelty: This study contributes a systematic spatial assessment of the Kokjar Basin’s natural features within the hierarchical framework of the Sangzor River Basin, emphasizing its dual potential for sustainable agriculture and eco-tourism development based on integrated basin management principles.